AI-POWERED INTELLIGENT SYSTEM MODEL FOR DEFECT DETECTION IN THE MANUFACTURING PROCESS OF ELECTRONIC COMPONENTS - Hery Sudaryanto; Muhammad Amanulloh Mz; Nur Ismianah (Adisam Publisher, 2026)
The rapid advancement of the electronics manufacturing industry demands extremely high precision to achieve zero-defect production standards. However, conventional manual inspection processes remain constrained by human fatigue, subjectivity, and limited inspection speed. To address these limitations, this study proposes an AI-powered intelligent inspection system based on Deep Learning for real-time defect classification in electronic component manufacturing. The proposed approach integrates a Convolutional Neural Network (CNN) architecture with an attention mechanism to enhance feature representation by focusing on defect-prone regions, such as soldering anomalies, missing components, and surface cracks. The research methodology encompasses a complete processing pipeline, starting from the utilization of a publicly available high-resolution PCB defect image dataset, followed by systematic data augmentation to mitigate class imbalance, and the application of a lightweight CNN-based feature extraction framework to support efficient inference. Experimental results demonstrate that the proposed model achieves a classification accuracy of 98.5%, outperforming conventional machine vision–based inspection approaches with a significantly lower false discovery rate. Furthermore, robustness evaluations indicate that the system maintains stable performance under varying lighting conditions and simulated production speeds. These findings confirm the effectiveness and scalability of the proposed intelligent inspection system as a practical solution for automated quality assurance in smart manufacturing environments.